Deteksi Dini Perubahan Nilai GDS pada Olahragawan dalam Upaya Pencegahan Penggunaan Doping - Siti Rahmani; Sri Wahyuni (Jurnal Keperawatan Silampari, 2022)
This study aims to see changes in GDS values in athletes to prevent doping use. This study uses quasi-experimental research with a one-group pre-test-post-test design. The results showed that the shift in GDS values in futsal players decreased by an average of 5 mg/dl, in swimmers, the standard decreased by 8 mg/dl, 100 M runners decreased by an average of 4 mg/dl, and the average value decreased in GDS values. On mobile legend e-sport players, only 1 mg/dl. In conclusion, the types of sports that experienced the most decrease in GDS occurred swimming, then futsal, 100 M running, and e-sports players. Blood glucose values will decrease more and more if a person does activities with more use of body movement. Cold temperatures will increase the body's ability to produce energy which will maintain body temperature within normal limits. Keywords: Doping, Blood Glucose During (GDS), Athlete